IMPLEMENTASI ALGORITMA BRUTE FORCE PADA PERANCANGAN APLIKASI KAMUS BAHASA SUNDA BERBASIS ANDROID - Anton Suryoprayogo, Sidiq (Jurnal Informatika dan Bisnis, 2016)
Mobile is an effective means of telecommunication . As time goes by and the growing world of information and technology , the mobile phone does not eliminate the main function metamorphosed into a multifunctional device . A variety of features and benefits added to a device that is easy to carry anywhere , many facilities in the mobile phone as an example ( camera , games , internet with GPRS and many more ) . From these aspects munculah an idea to create an application that is instructive as a means of learning a language is BahasaSunda Dictionary Application Design Based Android. Where everyone can learn a language and to help search for the names of Sundanese language term that can be used anytime , anywhere and at any time , in other words moving and flexible dictionary . At the end of this project made a mobile dictionary application for a more familiar term in the Sundaneselanguage , which is expected to produce applications that support learning , public and educational insights and can preserve local culture .Â Keywords : Brute Force Algorithm, Android Application, Application Dictionary